Spatial aluminium sensitivity of root apices of two common bean (Phaseolus vulgaris L.) genotypes with contrasting aluminium resistance - Rangel Becerra, Andrés Felipe; Rao, Idupulapati M.; Horst, Walter J. (Oxford University Press, 2007)
The initial response of plants to aluminium (Al) is an inhibition of root elongation. In the present study, short and medium-term effects of Al treatment (20??M) on root growth and Al accumulation of two common bean (Phaseolus vulgaris L.) genotypes, VAX-1 (Al-sensitive) and Quimbaya (Al-resistant), were studied. Root elongation of both genotypes was severely inhibited during the first 3 4?h of Al treatment. Thereafter, both genotypes showed gradual recovery. However, this recovery continued in genotype Quimbaya until the root elongation rate reached the level of the control (without Al) while the genotype VAX-1 was increasingly damaged by Al after 12?h of Al treatment. Short-term Al treatment (90??M Al) to different zones of the root apex using agarose blocks corroborated the importance of the transition zone (TZ, 1 2?mm) as a main target of Al. However, Al applied to the elongation zone (EZ) also contributed to the overall inhibition of root elongation. Enhanced inhibition of root elongation during the initial 4?h of Al treatment was related to high Al accumulation in root apices in both genotypes (Quimbaya>VAX-1). Recovery from Al stress was reflected by decreasing Al contents especially in the TZ, but also in the EZ. After 24?h of Al treatment the high Al resistance of Quimbaya was reflected by much lower Al contents in the entire root apex. The results confirmed that genotypic differences in Al resistance in common bean are built up during medium-term exposure of the roots to Al. For this acquisition of Al resistance, the activation and maintenance of an Al exclusion mechanism, especially in the TZ but also in the EZ, appears to be decisive.